EXPERIMENTAL PETROLOGY OF MELILITE NEPHELINITES - Gee Lauren L.; Sack Richard O. (My University, 1988)
Experimental study of natural melilite nephelinite lavas of intermediate K/Na ratio at low pressure (fo2 ∼ reveals the presence of a peritectic 'point' of distributary type (∼1090°C) for liquids saturated with leucite, nepheline, and spinel. With decreasing temperature on the olivine + melilite cotectic, both olivine and melilite react with such liquids to produce high-calcium pyroxene at the peritectic. Both the olivine + high-calcium pyroxene and melilite + high-calcium pyroxene cotectics are stable at temperatures below the peritectic. Olivines coexisting with such liquids are much more magnesian than those in comparable tholeiitic liquids. The olivine-liquid Fe-Mg distribution coefficient [KD Fe-MgOL-LIQ=(X/XFeOLIQ)/(XMg2SIO4OL/XFe2SIO4OL)] is a monotonically increasing function of silica activity over the composition range spanned by melilite nephelinite, ugandite, alkali basalt, and tholeiite basalt liquids. The analogous Fe-Mg distribution coefficient for melilite and liquid is effectively constant (KD Fe-MgMEL-LIQ=0c 23±0c 02), while that for high-calcium pyroxene and liquid is highly dependent on the chemistry of high-calcium pyroxene (cf., Sack & Carmichael, 1984). Pseudoternary liquidus projections of multiply saturated liquids coexisting with nepheline, leucite, and spinel (±olivine±high-calcium pyroxene±melilite) have been prepared to facilitate graphical analysis of the evolution of lava compositions during hypabyssal cooling. Major element chemical analyses and petrographic features of lavas from Mt. Nyiragongo, East Africa and Oahu, Hawaii (e.g., Denaeyer et al., 1965; Wilkinson & Stolz, 1983) confirm the validity of these diagrams and the systematics established from the experimental data.